2004
DOI: 10.1517/13543784.13.5.531
|View full text |Cite
|
Sign up to set email alerts
|

Gallium nitrate for the treatment of non-Hodgkin’s lymphoma

Abstract: Mortality from non-Hodgkin's lymphoma (NHL) is high, thus defining the need for additional therapeutic agents for this disease. Gallium nitrate is a metal compound that is presently approved for the treatment of hypercalcaemia associated with malignancy. In clinical trials first conducted over two decades ago, this drug was found to have antineoplastic activity in NHL. However, its development as an antineoplastic agent for the treatment of NHL was never rigorously pursued. Gallium has unique mechanisms of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…It has also shown efficacy against a diverse set of disorders such as accelerated bone resorption and autoimmune and infectious diseases (2). Gallium is currently approved for the treatment of hypercalcemia associated with malignancy (7)(8)(9). Besides its therapeutic utility, for over a half century, Ga 67 has been used as a diagnostic agent for cancer (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…It has also shown efficacy against a diverse set of disorders such as accelerated bone resorption and autoimmune and infectious diseases (2). Gallium is currently approved for the treatment of hypercalcemia associated with malignancy (7)(8)(9). Besides its therapeutic utility, for over a half century, Ga 67 has been used as a diagnostic agent for cancer (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…To attain more Fe, neoplastic cells express higher levels of the transferrin receptor 1 (TfR1) and take up Fe at a greater rate than their normal counterparts (1). This is reflected by the ability of tumors to be radiolocalized using 67 Ga, which binds to the Fe transport protein, transferrin, for delivery via TfR1 (3,4). Similarly, phosphorothiolated antisense TfR1 oligonucleotides targeted to TfR1 mRNA showed selective anticancer activity (5), confirming the importance of Fe in cancer cell growth.…”
mentioning
confidence: 99%
“…Hence, there remains a great need to develop novel agents for the treatment of this malignancy. In the late 1970s, the group IIIa metal salt gallium nitrate was discovered to have antitumor activity in animal tumor models, and in subsequent clinical trials, it proved to have significant antineoplastic activity against non-Hodgkin's lymphoma and urothelial malignancies (Warrell et al, 1983;Weick et al, 1983;Keller et al, 1986;Einhorn, 2003;Chitambar, 2004). A more recent clinical trial confirmed the efficacy of gallium nitrate in patients with nonHodgkin's lymphoma whose disease had relapsed following treatment with conventional chemotherapeutic agents (Pro et al, 2004).…”
mentioning
confidence: 99%